A structure zone diagram obtained by simultaneous deposition on a novel step heater: A case study for Cu2O thin films. Issue 12 (7th August 2015) - Stein, Helge; Naujoks, Dennis; Grochla, Dario; Khare, Chinmay; Gutkowski, Ramona; Grützke, Stefanie; Schuhmann, Wolfgang; Ludwig, Alfred
Abstract : In thin film deposition processes, the deposition temperature is one of the crucial process parameters for obtaining films with desired properties. Usually the optimum deposition temperature is found by conducting several depositions sequentially in a time consuming process. This paper demonstrates a facile and rapid route of the simultaneous thin film deposition at six different deposition temperatures ranging from 100 to 1000 °C. Cuprite (Cu2 O) was chosen for the study as this material is of interest for energy applications. The thin films are assessed for their crystallographic, microstructural, Raman scattering, and photoelectrochemical properties. The results show that the utilization of a step heater leads to the rapid optimization of thin film microstructures of an absorber material used in photoelectrochemistry. This results in a structure zone diagram for Cu2 O. For a substrate temperature of 600 °C, an optimum between crystallinity and morphology occurs.